Occupational Ergonomics and Safety, Part 1 - Arezes, P. (2015)
[Excerpt] It seems that significant progress has been made in last years in what concerns the scientific knowledge about work and its impact on workers’ wellbeing and health, which includes but it is not limited to occupational ergonomics and safety. Even considering that this domain is very transversal and comprehensive, as it may include researchers from multidisciplinary teams, research in this domain has clearly increased and we have now a larger number of scientific events, a higher number of researchers publishing their works, and a high emergence rate of research groups at universities and other research institutions, which was also followed by an increasing concern about these issues by governments and other regulators. Even though it is strikingly difficult to demonstrate it in an unequivocal way, this appears to have had a clear effect on companies and on their ability to implement plans and measures to prevent and control occupational risk factors. But despite these advances, occupational risk prevention is still a domain for which solutions are neither complete nor permanent, since the evolution of work systems gives rise to new challenges.